Designing workforce management systems for industry 4.0 data-centric and AI-enabled approaches - Khang, Alex; Rani, Sita; Gujrati, Rashmi (CRC PRESS, 2024)
This book brings insight to the HR management system and offers data-centric approaches and AI-enabled applications for the design and implementation strategies used for workforce development and management. Designing Workforce Management Systems for Industry 4.0: Data-Centric and AI-Enabled Approaches focuses on the mechanisms of proposing solutions along with architectural concepts, design principles, smart solutions, and intelligent predictions with visualization simulation. Data visualization for the metrics of management systems and robotic process automation applications and tools are also offered. This book is also useful as a reference for those involved in AI-enabled applications, data analytics, data visualization, as well as systems engineering and systems designing